2021
DOI: 10.3846/jbem.2021.14181
|View full text |Cite
|
Sign up to set email alerts
|

Elements Indicating Stock Price Movements: The Case of the Companies Listed on the V4 Stock Exchanges

Abstract: Stock markets stand as a financial mechanism that provides liquidity for firms and offers diversification benefits for investors. Stock markets in the Eastern European countries are weakform efficient which exposes them to speculative prices. This study investigates the influence of the macroeconomic and firm-specific factors on stock prices of the listed companies within the Visegrad Stock Markets. The study employs regression analyses based on a Pooled OLS and Fixed Effect models with year dummies and standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Aliu's research found that total share capital is an important factor affecting stock prices, and an increase in stock supply will lower stock prices. The impact of exchange rates and inflation on stock prices is relatively weak, and important indicators such as debt, cash flow, oil, and gold prices have a relatively small impact on stock price fluctuations [36]. Compared to larger firms, smaller firms are more flexible and agile during the growth phase, able to adapt quickly to changes in market demand, and have more opportunities to generate higher growth rates.…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%
“…Aliu's research found that total share capital is an important factor affecting stock prices, and an increase in stock supply will lower stock prices. The impact of exchange rates and inflation on stock prices is relatively weak, and important indicators such as debt, cash flow, oil, and gold prices have a relatively small impact on stock price fluctuations [36]. Compared to larger firms, smaller firms are more flexible and agile during the growth phase, able to adapt quickly to changes in market demand, and have more opportunities to generate higher growth rates.…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%
“…9770/jesi.2022.10.2(30) al., 2022Androniceanu et al, 2020;Simionescu et al, 2021). The work by Aliu et al (2021) shows that due to financial literacy, macroeconomic and firm-specific factors are hardly priced into these exchanges. The structure of the firms in the PX Index is constantly changing while few of them exist since its foundation (PSE, 2022).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Prices are important signals for market participants as they allow efficient allocation of resources. The stock prices reflect expectations for the future and current financial position of the listed firms (Nuhiu et al , 2022; Aliu et al , 2021). The market mechanism of equity stocks mostly removes inefficient entities from their system by adjusting the excesses.…”
Section: Introductionmentioning
confidence: 99%